2018
DOI: 10.1159/000486413
|View full text |Cite
|
Sign up to set email alerts
|

Can a Non-Native Primate Be a Potential Seed Disperser? A Case Study on Saimiri sciureus in Pernambuco State, Brazil

Abstract: The interaction between native fleshy-fruit plants and introduced fruit consumers contributes to the dynamics of highly fragmented environments. Such interactions can occur through pollination and seed dispersal. Here, we investigated the potential of seed dispersing by a non-native primate, the squirrel monkey (Saimiri sciureus), in an urban Atlantic forest fragment in north-eastern Brazil. Fleshy fruits from non-native plants were preferentially exploited by the squirrel monkeys. We measured 147 seeds (width… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…2009, Oliveira‐Silva et al. 2018) contained papers that studied the ecological processes explicitly. Other topics such as Urban ecology (e.g., van Rensburg et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2009, Oliveira‐Silva et al. 2018) contained papers that studied the ecological processes explicitly. Other topics such as Urban ecology (e.g., van Rensburg et al.…”
Section: Discussionmentioning
confidence: 99%
“…A closer look at the other topics revealed that this distinction can be made between several other topics. For example, some topics, such as Carrion ecology (e.g., Mashaly andAl-Mekhlafi 2016, Altunsoy et al 2017) and Ecosystem services for plants (e.g., Twigg et al 2009, Oliveira-Silva et al 2018) contained papers that studied the ecological processes explicitly. Other topics such as Urban ecology (e.g., van Fig.…”
Section: Function Vs Biodiversitymentioning
confidence: 99%
“…Aust. 27(1):73-87, 2023 mm) cut into squares with an area of 1 m² (Oliveira-Silva et al 2018). They were tied with string to native trees present at the site, 1 ½ meters above the ground.…”
Section: Evaluation Of Seed Rainmentioning
confidence: 99%
“…The other syndromes can be categorized as seeds dispersed by abiotic means (winged seeds, seeds with plumes, dispersed by wind or by the explosion of the fruits). We performed this characterization based on our knowledge about the previously described local plant community in the study areas (Sousa Júnior 2006, Lins-e-Silva & Rodal 2008, Campêlo et al 2018, Oliveira-Silva et al 2018, and from details about life-history traits of the species from the literature (Souza & Lorenzi 2008).…”
Section: Dispersal Syndromes and Ecological Groupsmentioning
confidence: 99%
See 1 more Smart Citation